2022
DOI: 10.31486/toj.22.0064
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Efficiency of Sugammadex Following Laparoscopic Cholecystectomy in Clinical Practice

Abstract: Background: Studies have proposed that the routine use of the modified gamma-cyclodextrin, sugammadex, could provide perioperative time savings. However, these investigations have been limited to small group analyses. The purpose of this study was to test the effectiveness of sugammadex on perioperative times when compared to neostigmine under general clinical practice conditions following rocuronium-induced neuromuscular blockade for laparoscopic cholecystectomy. Methods: Following institutional review board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 34 Although sugammadex was associated with shorter operating room times of ∼12.5 minutes, the time savings with sugammadex were largely associated with shorter surgical times. 34 We conducted a post hoc analysis of reversal agents by surgical times 35 and found that as surgical times for laparoscopic cholecystectomy increased, a higher percentage of sugammadex was used for reversal of rocuronium-induced neuromuscular blockade ( Figure 1 ). Lower median and interquartile range [IQR] surgical times for neostigmine (53 [IQR 39-75] minutes) were observed when compared to sugammadex (64 [IQR 42-99] minutes) surgical times (chi-square=120, P <0.0001).…”
Section: Initial Studies With Sugammadexmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 Although sugammadex was associated with shorter operating room times of ∼12.5 minutes, the time savings with sugammadex were largely associated with shorter surgical times. 34 We conducted a post hoc analysis of reversal agents by surgical times 35 and found that as surgical times for laparoscopic cholecystectomy increased, a higher percentage of sugammadex was used for reversal of rocuronium-induced neuromuscular blockade ( Figure 1 ). Lower median and interquartile range [IQR] surgical times for neostigmine (53 [IQR 39-75] minutes) were observed when compared to sugammadex (64 [IQR 42-99] minutes) surgical times (chi-square=120, P <0.0001).…”
Section: Initial Studies With Sugammadexmentioning
confidence: 99%
“…These analyses support the hypothesis 34 that in cases with longer surgical times, sugammadex may allow for faster completion of surgery as the number of studentized sugammadex outliers was less ( Figure 2 ). Nevertheless, in the study by Lee, Ahsan, Chae, et al, 35 the authors explored the perioperative efficiency of this gamma-cyclodextrin for improving operating room discharge and postanesthesia care unit recovery times without favorable results.…”
Section: Initial Studies With Sugammadexmentioning
confidence: 99%